The Outlook for agriculture and rural development in the Americas : a perspective on Latin America and the Caribbean 2015-2016 (IICA San JoséCR, 2015)
Presents recommendations for policies that are needed to enable the region's agriculture to regain its former buoyance and to enhance the development of rural areas.
Keywords: AGRICULTURE